Analysis of Wind Energy Potential and Technical Evaluation of a Small-Scale Wind Turbine for Electricity Generation in Batam, Indonesia - Hasibuan ST.MT, Fardin; syaputra, Muhammad Lyan; irsyam, Muhammad; faturahman, noval; kuniawan, Muhammad iman (METALOGRAM, 2025)
Wind energy represents one of Indonesia’s most promising renewable energy resources, with a national potential estimated at approximately 60 GW. However, its implementation remains limited due to insufficient site-specific assessments and feasibility studies. This research analyzes the wind energy potential at Galang District Beach, Batam City, and evaluates the technical suitability of the Sky Dancer 500 (TSD 500) wind turbine equipped with inversed-taper blades for small-scale electricity generation. A descriptive quantitative method was employed using secondary wind speed data from NASA (2014–2018) and primary measurements collected continuously for 30 days. Results show that Galang District Beach, Batam City exhibits average wind speeds ranging from 4 to 13.41 m/s, with a maximum recorded speed of 13.41 m/s. Based on technical analysis, low-speed wind characteristics align well with the operational profile of a horizontal-axis wind turbine utilizing inversed-taper blades. Estimations indicate that the TSD 500 turbine can generate 390–500 Wh of electricity per day under the observed wind conditions. These findings demonstrate that the site possesses adequate potential for micro-scale wind power development, and deploying ten units of the TSD 500 turbine could supply daily electrical needs for approximately ten households. The study contributes to the growing body of literature on decentralized renewable energy solutions for remote and coastal communities in Indonesia..